Pengaruh Remunerasi, Motivasi, dan Kepuasan Kerja Pegawai Pengadilan Agama Baturaja (Ekonomika, 2020)
This research aims to analyze the effect of remuneration, motivation, and job satisfaction on the performance of employees of the Baturaja Religious Court. The author conducted research using Multiple Linear Regression analysis tools, with the help of SPSS 24. The technique for data was through a questionnaire with a Likert scale. Before the analysis, the authors conducted a validity test and a reliability test so that the data obtained were valid and reliable. From the results of the regression equation analysis Y = - 1.255 + 0.420X1 + 0.674X2 + 0.358X3. Hypothesis testing shows that Remuneration, Motivation, and Job Satisfaction have an effect on Employee Performance at the Baturaja Religious Court, either partially or simultaneously. Analysis of the coefficient of determination (R2) is 0.954, which means that the variables of Remuneration, Motivation, and Job Satisfaction contribute to Employee Work Effectiveness by 95.4% while the remaining is 4.6% or varied by other variables not examined in this study.